Pemanfaatan Koleksi Perpustakaan oleh Pelajar di Dinas Perpustakaan dan Kearsipan Kabupaten Sijunjung - Ariri, Aulia Azzima; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper about the use of library collections by students in the Sijunjung Regency Library and Archives Service aims to find out internal and external factors that influence students in utilizing library collections in the Sijunjung District library and Archives Office. This type of research used in this study is a descriptive study using a quantitative approach, data collection techniques through the distribution of questionnaires to students who visit the library at the Library and Archives Office questionnaire distribution is done accidentally (accidental sampling). Based on the data that is processed, it can be concluded that the use of library collections is influenced by internal factors in terms of user needs, namely the frequency of students visiting on average once a week (38.5%) where students use to read (50%), students say they are satisfied visit the library because they get the information needed (60%). In terms of user motives (88%) students said books in the library were very helpful for doing school work. In terms of user interest the average length of time to visit (26%) students answered 1/2 hour each time they visited. Utilization of library collections is influenced by external factors in terms of collection completeness (66%) students use collections by borrowing, (88%) students say they agree about completeness of collections in the library. In terms of the skills of librarians in serving users (58%) students said the actions of librarians directing the location of bookshelves to students who had difficulty finding books needed, (59.3%) students said the attitude of the librarian was friendly. In terms of the availability of information retrieval facilities, the way students look for collections (86%) said directly to books, (67%) students said that it was necessary to improve computer facilities to access the internet in the library.Keywords: Utilization, Library, Collection, Students